2019
DOI: 10.1101/19000463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Updating Insights into Rosiglitazone and Cardiovascular Risk through Shared Data: Individual Patient- and Summary-Level Meta-Analyses

Abstract: Objective: To conduct a systematic review and meta-analysis of the effects of rosiglitazone therapy on cardiovascular risk and mortality using multiple data sources and varying analytical approaches. Design: Systematic review and meta-analysis of randomized controlled trials. Data sources: GlaxoSmithKline's (GSK) Clinical Study Data Request (CSDR) and Study Register platforms, MEDLINE, PubMed, Embase, Web of Science, Cochrane Central Registry of Controlled Trials, Scopus, and ClinicalTrials.gov from inception … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Rosiglitazone increases plasma LDL-C and HDL-C levels [ 161 ], whereas pioglitazone improves dyslipidemia by increasing plasma HDL-C levels and decreasing plasma TG levels without raising LDL-C [ 162 ] or increasing large, buoyant LDL [ 161 , 163 ]. While long-term rosiglitazone treatment of T2D patients may slightly increase the risk of myocardial infarction [ 164 ], pioglitazone somewhat decreases the risk of MACE (although the risk of heart failure increases with all glitazones) [ 165 , 166 ]. In biopsy-proven NASH patients, rosiglitazone treatment did not modify plasma TG or HDL-C levels but increased LDL-C [ 156 ].…”
Section: Therapeutic Strategies and Their Potential Impact On Cvd Rismentioning
confidence: 99%
“…Rosiglitazone increases plasma LDL-C and HDL-C levels [ 161 ], whereas pioglitazone improves dyslipidemia by increasing plasma HDL-C levels and decreasing plasma TG levels without raising LDL-C [ 162 ] or increasing large, buoyant LDL [ 161 , 163 ]. While long-term rosiglitazone treatment of T2D patients may slightly increase the risk of myocardial infarction [ 164 ], pioglitazone somewhat decreases the risk of MACE (although the risk of heart failure increases with all glitazones) [ 165 , 166 ]. In biopsy-proven NASH patients, rosiglitazone treatment did not modify plasma TG or HDL-C levels but increased LDL-C [ 156 ].…”
Section: Therapeutic Strategies and Their Potential Impact On Cvd Rismentioning
confidence: 99%
“…There are significant limitations to investigating MACE using meta-analyses of RCTs that are designed for efficacy. Serious adverse events may not be reported or measured systematically, as illustrated by the time it took to report the increased risk of MACE from rosiglitazone in type 2 diabetes mellitus [41]. Adjudication committees are often convened for predefined serious adverse events of special interest, which may not be the case if concern regarding MACE was not known prior to the initiation of the phase III RCTs.…”
Section: Limitations To Rcts and Meta-analyses For Interpretation Of Biologic-related Cardiovascular Riskmentioning
confidence: 99%
“…Similar safety concerns resulted in some restrictions in the use of rosiglitazone; however, its use was not banned in United States (Cohen, 2010). Moreover, recent meta-analysis identified that rosiglitazone is associated with an increased cardiovascular risk, especially for heart failure events (Wallach et al, 2020). Another aspect of PPAR-γ biology that holds back their clinical use is that PPAR-γ receptors play role in bone homeostasis mechanisms, which is likely why they contribute to bone fractures seen in patients (Wei & Wan, 2011).…”
Section: P Otential For Clinic Al Tr An S L Ati On Of Ppar Ag Onis Tsmentioning
confidence: 99%